The TNF-α-308G/A polymorphism is associated with migraine risk: A meta-analysis - GU, LIAN (D.A. Spandidos, 2012)
Migraine is a neurasthenia and the genetic etiology has not been determined. Several studies concerning the correlation between the tumor necrosis factor (TNF)-α-308G/A polymorphism and migraine have been published, but their results remain controversial and the small samples in each study do not allow sufficient statistical power. In the present study, odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength of the association between the polymorphism and migraine. An inverse-variance method was applied to estimate the frequency of the putative risk allele in the controls. Heterogeneity was determined using Cochran’s Q test and the inconsistency index (I(2)). Begg’s test and the inverted funnel plot were used to assess the publication bias. Five studies on Asian populations, comprising 985 cases and 958 controls, were included in the meta-analysis. The overall results revealed that the TNF-α-308G/A polymorphism was associated with migraine risk in Asians. The ORs were 1.735 (95% CI, 1.129–2.666) for A vs. G; 1.781 (95% CI, 1.166–2.718) for GA vs. GG; 1.821 (95% CI, 1.153–2.874) for AA+GA vs. GG. The subgroup analysis was based on migraine with aura (MA) and migraine without aura (MO) and there was a statistically significant result for MA [the OR was 1.728 (95% CI, 1.095–2.726) for GA vs. GG and 1.651 (95% CI, 1.049–2.598) for AA+GA vs. GG] but not for MO. In conclusion, the TNF-α -308G/A polymorphism was associated with migraine risk.